Love in the Times of COVID-19: Centered in Older Persons Care - Parodi, José F. (2020)
Older adults are the most vulnerable population group in the COVID-19 pandemic. Not only do they have the highest mortality, multimorbidity, and various problems during the pandemic, but they will have the greatest number of needs after it. To guarantee human rights, optimize the healthy aging process and center attention in person, the state and society in general will require a series of extraordinary measures.